Therapeutic hypothermia in Post - cardiac arrest : It is time to revisit the guidelines. - Shirin, Afroz; Islam, Tasbirul (Bangladesh Critical Care Journal, 2018)
Background: Targeted Temperature Management (TTM), previously known as therapeutic hypothermia is an important tool for prevention and reversal of neurological injury and mortality reduction. Over the recent period, the use of induced hypothermia has raised many questions and recent large, randomized controlled trials (RCTs) have failed to demonstrate the benefit of TTM on clinical outcomes. The objective of this article was to compare different studies on neurological outcomes after use of TTM in different clinical situations, different temperatures and rates of cooling. Methods: We incorporated studies from 1950s to recent years using search engines like PubMed, Science Direct, Google Scholar. Results: Initial two small, unblinded trials have demonstrated improved neurological outcome in out of hospital shockable cardiac arrest. Recent studies showed that TTM was not associated with higher rates of survival or favorable neurological outcome in patients with IHCA and was rather associated with potential harm, lower likelihood of survival after discharge and long term neurological survival. TTM also didn’t show any favorable results in non-shockable cardiac arrests. Hypothermia of 36°C did not confer much benefit over 32°C -34°C. Conclusion: Recent large studies didn’t show no strong evidence that TTM is highly effective. Further methodologically robust studies are required in both shockable and non-shockable cardiac arrest for TTM to have any effect on neurological outcome. Bangladesh Crit Care J September 2018; 6(2): 84-87